Linear and nonlinear Granger-causality between short-term and long-term interest rates during business cycles. Issue 6 (1st November 2016) - Rahimi, Azadeh; Lavoie, Marc; Chu, Ba
Abstract: This paper is about the causal relationship between short-term and long-term interest rates in the US and Canada. To that end, we apply a linear Granger causality test introduced by Toda and Yamamoto (1995 ) and the nonlinear Granger causality test of Diks and Panchenko (2006 ). By combining linear causality effects with the nonlinear ones, it is seen that the most common Granger causality direction between short-term and long-term interest rates is a bidirectional one. We also find that nonlinear Granger causality can be found where no linear causality had been uncovered. Moreover, our findings show that during recent business cycles, the federal funds rate (in the US) and the overnight rate (in Canada) still Granger-cause long-term interest rates significantly.